DELINIATION OF HYDROCARBON POTENTIAL DISTRIBUTION IN CENTRAL SUMATERA BASIN RIAU PROVINCE USING GRAVITY METHOD - Akbar 'Alim, Rais
The Central Sumatra Basin is a sedimentation basin located in the middle of the island of Sumatra, Indonesia. The Central Sumatra Basin is known as one of the areas that has potential natural resources, such as petroleum and natural gas. The gravity method is an exploratory method in the discipline of geophysics that allows us to obtain information about the subsurface structure of the earth. This method is done by measuring the acceleration of gravity in the study area and determining physical parameters such as variations in density contrast in rocks or materials below the surface. This method is useful in finding natural resources that have the potential to be contained in the research area. This Final Project will discuss the use of gravity method in delineation of hydrocarbon potential distribution. The purpose of this study is to determine the distribution of gravitational field anomaly values, estimation and implications of sediment thickness, and the mechanism and geometry of structural traps in the Central Sumatra Basin area of Riau Province. The data used in this study are secondary data obtained from the Geological Survey Center (PSG). The data is in the form of Bouguer anomaly comple values in the study area that have gone through a series of corrections such as drift, tide, latitude, free air, Bouguer, and topography. After that, the complete Bouguer anomaly data were separated into regional anomalies and residual anomalies through spectrum analysis and filtering using the Butterworth Filter. The result of this study is a complete distribution map of Bouguer anomaly with values ranging from 11,512 mGal to 27,555 mGal. This study also succeeded in determining the depth of regional zones and residual zones in the study area, which is about 12,788 kilometers and 6,886 kilometers respectively. At the modeling stage, threedimensional inversion modeling is used by including seismic cross-sectional data to determine the potential of hydrocarbons in the study area.